Food Quality, Calories, and Household Income - Skoufias, Emmanuel; Di Maro, Vincenzo; González-Cossío, Teresa; Rodríguez Ramirez, Sonia (Taylor and Francis, 2013)
We investigate the relationship between calories, food quality and household per capita expenditure using regression and semiparametric methods on a sample of poor households from rural Mexico, where Programa de Apoyo Alimentario (PAL), a targeted nutritional programme, is operating. The semiparametric method yields an estimate of the elasticity between calories and expenditure of 0.39 below the median and 0.28 above. The corresponding estimates of the elasticity of the calorie price are 0.48 below the median and 0.45 above. We also examine the extent to which the expenditure elasticity of the calorie price is explained by substitution between and within major food groups. We find that there is a very high incidence of substitution within cereals (especially for poor households) and that between group substitution explains at most 59% of the income elasticity for food quality. These estimates suggest that the potential of a cash transfer programme to have a positive impact on the food diversity and the nutritional status of households is quite limited.